Science, politics and society in early nineteenth-century Ireland : the Reverend William Richardson - Blackstock, Allan (Manchester University Press, 2013)
Based on newly unearthed source material, this book follows the career of clergyman William Richardsona and assesses his impact on politics, science and agriculture nationally and internationally.